Endohedral Metallofullerenes: An Ideal Platform of Sub‐Nano Chemistry - Shen, Wangqiang; Bao, Lipiao; Lu, Xing (Chinese journal of chemistry, 2022)
Comprehensive Summary The hollow cavity of fullerenes is an ideal host for the stabilization of a variety of otherwise unstable metallic clusters, enabling the discovery of novel compounds and unconventional metal‐metal and metal‐carbon interactions. Meanwhile, the internal metallic species exert interesting influences on the chemical properties of the cage carbons, mainly through electronic interactions, leading to unexpectedly high regioselectivity and high yield, and even quantitative conversion. What is the most favorite and original chemistry developed in your research group? Creation of novel metal‐carbon hybrid molecules with unconventional techniques, known as endohedral metallofullerenes, and the unexplored chemistry hidden inside them, especially discovery of the unprecedented bonding between rare earth metal ions and a variety of novel metal clusters, e.g., Ti3C3 and Dy2N4. How do you get into this specific field? Could you please share some experiences with our readers? I entered the field of fullerenes when I was pursuing my Ph.D. during 2001—2004 in Peking University. At that time, fullerenes are no longer a hot research subject as carbon nanotubes which have shown huge perspectives in both fundamentals and applications. However, I like fullerenes because of their clear structures and readily high solubility in organic solvents, which are rather attractive to chemists. I have been working in this field for nearly twenty years and my feeling is that interest and passion are the most important characteristics for a scientist to keep finding in a seemingly out‐of‐date field. What are your hobbies? What are your favorite books? Badminton is my favorite sport in addition to jogging, and reading historical novels and essays is a hobby during my leisure time. My favorite books are “Romance of the Three Kindoms”, “War and Peace”, “A Dream of Red Mansions” and “One Hundred Years of Solitude”. How do you supervise your students? As every student has his/her own talents so that I treat each as individuals to express their own merits as much as possible. In addition, the graduate students in my lab do not only learn about the detailed experimental skills but also the way how to find solutions to the scientific problems they are facing, namely thinking modes to solve problems. In detail, I request my students to ensure their time and energy in experiments and research works daily, as diligence is the magic weapon of success, in addition to persistence and enthusiasm. How do you keep balance between research and family? My motivation of hard‐working comes from my family so that I concentrate on my work during working time every day, but I try my best to stay with my kids on weekends and leisure time to replenish my energy. Could you please give us some advices on improving Chinese Journal of Chemistry? This journal should cover all categories of chemistry, keeping balance among organic, inorganic, materials, analytical and others, instead of focusing too much on organic and synthetic chemistry. Endohedral metallofullerenes (EMFs), namely fullerenes with metallic species encapsulated inside, represent an ideal platform to investigate the metal‐metal or metal‐carbon interactions at the sub‐nanometer scale. Moreover, as a result of the interplay between the internal and external units, the chemical properties of EMFs, controlled by both the electronic and geometric effects, are particularly intriguing compared to those of empty fullerenes.